(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A series of composites of carbon fibre-reinforced polyamide1012 (PA1012) were prepared which the carbon fibre content was from 5% to 40%. Their thermo-mechanical properties and fracture morphology were characterized by means of thermogravimetric analysis (TGA), a microcomputer-controlled electronic universal tester, and Scanning Electron Microscopy (SEM), respectively. The results showed that the initial decomposition temperature of the composite was above 400C. With the increase in carbon fibre content, the tensile strength and elastic modulus of the composites were improved. When the carbon fibre content was 15%, it was found that the maximum values of tensile strength and elastic modulus were 87.01 MPa and 438.31 MPa, respectively. The images of SEM showed that the surface modified carbon fibre was superior to original carbon fibre. It was also observed that the surface of modified carbon fibre had some particles that may have contained the ester group, which could have improved the interfacial bonding strength.